PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS STEM PADA MATERI FLUIDA DINAMIS KELAS XI SMA - Adiella Zakky Juneid; Fakhruddin Fakhruddin; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research is to develop STEM-Based learning media on dynamic fluid material kelas XI SMA that valid. This type of research uses Research and Development (R&D) with the ADDIE model. The learning media developed is divide into experimental set device and student’s worksheet and were made for 3 experiments. The data was collected through a validation assessment sheet for experimental set devide and student’s worksheet that was assessed by the validator. The aspects of experimental set device that were assessed included aspects of device function, learning elements, convenience, aesthetics and construction, and job security. While the aspects of student’s worksheet that were assessed included aspects of the accuracy of the content, presentation, and appearance. The results of the validation of experimental set device and student’s worksheet obtained an average >3. Thus it can be concluded that the STEM-Based learning media on dynamic fluid material Kelas XI SMA is declared valid.Keywords: Learning Media, STEM, Experimental Set Device, Student’s Worksheet, Dynamic Fluid